2017
DOI: 10.1093/gbe/evx091
|View full text |Cite
|
Sign up to set email alerts
|

Transposable Element Misregulation Is Linked to the Divergence between Parental piRNA Pathways in Drosophila Hybrids

Abstract: Interspecific hybridization is a genomic stress condition that leads to the activation of transposable elements (TEs) in both animals and plants. In hybrids between Drosophila buzzatii and Drosophila koepferae, mobilization of at least 28 TEs has been described. However, the molecular mechanisms underlying this TE release remain poorly understood. To give insight on the causes of this TE activation, we performed a TE transcriptomic analysis in ovaries (notorious for playing a major role in TE silencing) of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
35
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 129 publications
(196 reference statements)
12
35
4
Order By: Relevance
“…Moreover, host TE suppression mechanisms can contribute to the inactivation and subsequent degeneration of TE copies over time, independently of the cellular mechanism of asexuality [75,86]. Similarly, we did not find any difference in TE content according to hybrid versus intraspecific origin of asexuals ( Supplementary Figure 7), even though mismatches between species-specific TEs and silencing machineries can result in increased TE activity in hybrids [12,14,[87][88][89].…”
Section: Transposable Elementssupporting
confidence: 49%
“…Moreover, host TE suppression mechanisms can contribute to the inactivation and subsequent degeneration of TE copies over time, independently of the cellular mechanism of asexuality [75,86]. Similarly, we did not find any difference in TE content according to hybrid versus intraspecific origin of asexuals ( Supplementary Figure 7), even though mismatches between species-specific TEs and silencing machineries can result in increased TE activity in hybrids [12,14,[87][88][89].…”
Section: Transposable Elementssupporting
confidence: 49%
“…Thus, our results suggest that TEs located nearby these genes could play an important role in xenobiotic stress response. Although there is not a clear association between the presence/absence of these TE insertions and the change in expression of their nearby genes (electronic supplementary material, table S4C), this result is consistent with previous analysis showing that the effect of TEs on the expression of nearby genes is background dependent [39,94]. More genetic backgrounds should be analysed to elucidate whether TEs have a specific effect restricted to particular backgrounds or whether the effect of TEs is more general.…”
Section: Discussionsupporting
confidence: 88%
“…The above results could be explained by a decrease of piRNA amounts in hybrids, but our recent results showed that piRNA amounts in hybrids resemble those of the parental species with higher production [27]. This trend towards high piRNA production in hybrids suggests that the piRNA pathway might be more efficient in hybrids, which could be explained by an increase in piRNA pathway genes expression.…”
Section: Introductionmentioning
confidence: 77%
“…These TE bursts have been associated with abnormal TE expression patterns, first of the retrotransposons Osvaldo and Helena [25,26] and then in a global transcriptomic study including the whole-genome TEs [27]. Importantly, these studies proved that (i) more TE families are misregulated in F1 ovaries than in the subsequent generations of backcrossed hybrids [27], (ii) TE expression is heterogeneous between hybrid samples from different interspecific crosses [25], and (iii) there are differences in transposition rates even between hybrids of the same cross [22].…”
Section: Introductionmentioning
confidence: 99%